1905
DOI: 10.1002/aja.1000040203
|View full text |Cite
|
Sign up to set email alerts
|

The development of the thoracic vertebræ in man

Abstract: WITH 7 PLATES.There is a somewhat extensive literature dealing with the development of the spinal column in various vertebrates. The chief stages in its differentiation are fairly well determined. Special attention has been given to the early development in the lower vertebrates. The recent literature on this subject up to 1897 h q been reviewed by Gaupp, 97.l Somewhat less attention hm been devoted to the mammals. To Proriep, 86, is due a valuable account of the development of the cervical vertebm in the cow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

1905
1905
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 2 publications
2
19
0
1
Order By: Relevance
“…Thus, he concluded that the vertebral column had changed its scgmentation during the early development and he called it 'hew segmentation (Neue Gliederung)". Many papers on the development o f the vertebral column were produced thereafter (Bardeen & Lewis 1901, Bardeen 1905, Keyes & Compere 1932, Wyburn 1944, Sensenig 1949, and Peacock 1951. Sensenig (1949) carried out the last extensive study on which the current concepts of the vertebral development seem to be based.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, he concluded that the vertebral column had changed its scgmentation during the early development and he called it 'hew segmentation (Neue Gliederung)". Many papers on the development o f the vertebral column were produced thereafter (Bardeen & Lewis 1901, Bardeen 1905, Keyes & Compere 1932, Wyburn 1944, Sensenig 1949, and Peacock 1951. Sensenig (1949) carried out the last extensive study on which the current concepts of the vertebral development seem to be based.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, Junghanns' basic concept that the cartilaginous anlage of the vertebral body consists of two lateral halves was not observed in our study ( Figure 8). Although Bardeen (1901Bardeen ( , 1905 described two chondrification centres of the vertebral body divided by the perichordal septum, no descriptions of it can be found in the later literature (Keyes & Compere 1932, Wyburn 1944, Sensenig 1949. Secondly, failure of formation is already present in the very early stage of chondrification in our embryo of 13 mm C-R length (6 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the trunk region of Bos, the primordia of the vertebral bodies are derived from the caudal half of one sclerotome and the cranial half of the next posterior sclerotome. Weiss (1901) identified the fissure in the rat, Schauinsland (1906) and Piiper (1928) found it in birds, and Bardeen (1905) observed it in the human embryo, noting that it appeared after the disappearance of the myoccele, at the end of the 3rd week.…”
Section: Remak (1855) Was the First To Draw Attention To The Resegmenmentioning
confidence: 99%
“…R obin (1864) rejected this idea and maintained that the circular appearance of the rudiment of the body of a vertebra is specific for the mammalian embryo. Froriep (1886) and Bardeen (1905) found suggestions of this bilateral origin, the centrum rudiment at first consisting of a pair of lateral masses subchordally united by means of a strand of pro-cartilage, the whole appearing as a U-shaped structure. In Mus this U-shape is characteristic, and in the case of the axis, the earliest rudiment of the centrum shows no subchordal connection and is therefore truly bilateral.…”
Section: And Not --- Because J-a = -----------------------mentioning
confidence: 99%